Widespread excess ice in Arcadia Planitia, Mars. Issue 16 (26th August 2015) - Bramson, Ali M.; Byrne, Shane; Putzig, Nathaniel E.; Sutton, Sarah; Plaut, Jeffrey J.; Brothers, T. Charles; Holt, John W.
Abstract: The distribution of subsurface water ice on Mars is a key constraint on past climate, while the volumetric concentration of buried ice (pore‐filling versus excess) provides information about the process that led to its deposition. We investigate the subsurface of Arcadia Planitia by measuring the depth of terraces in simple impact craters and mapping a widespread subsurface reflection in radar sounding data. Assuming that the contrast in material strengths responsible for the terracing is the same dielectric interface that causes the radar reflection, we can combine these data to estimate the dielectric constant of the overlying material. We compare these results to a three‐component dielectric mixing model to constrain composition. Our results indicate a widespread, decameters‐thick layer that is excess water ice 10 4 km 3 in volume. The accumulation and long‐term preservation of this ice is a challenge for current Martian climate models. Key Points: Terraced craters: abundant in Arcadia Planitia, indicate subsurface layering A widespread subsurface interface is also detected by SHARAD Combining data sets yields dielectric constants consistent with decameters of excess water ice